Clinical characteristics of pre-attack symptoms in cluster headache: A large series of Korean patients. (February 2021) - Cho, Soohyun; Cho, Soo-Jin; Lee, Mi Ji; Park, Jeong Wook; Chu, Min Kyung; Moon, Heui-Soo; Chung, Pil-Wook; Sohn, Jong-Hee; Kim, Byung-Su; Kim, Daeyoung; Kim, Jae-Moon; Chung, Jae Myun; et al.
Background: Previous studies have reported notable differences in demographic and clinical features of cluster headache between Western and Asian populations, including lower prevalence of the chronic type and in women. Recently, prodromal symptoms of migraine and pre-attack symptoms of cluster headache have drawn attention regarding their potential pathophysiological implications and pre-emptive treatment. However, pre-attack symptoms of cluster headache have not been studied in the Asian population. Methods: A total of 136 patients with cluster headache (21 first-onset, 110 episodic, and five chronic cases) were recruited in this multi-center study between October 2018 and December 2019. We evaluated the characteristics of pre-attack symptoms in a current bout using a structured questionnaire. Univariable and multivariable logistic regression analyses were performed to evaluate the factors associated with presence of pre-attack symptoms. Results: Pre-attack symptoms were reported in 71.3% of our patients with cluster headache. When present, pre-attack symptoms occurred at a median of 20 minutes (range 1–120) before the attack. The prevalence of local and painful, local and painless sensory, autonomic, and general symptoms was 58.8%, 14.7%, 11.0%, and 30.1%, respectively. Multivariable logistic regression analysis revealed that higher number of bouts was associated with higher prevalence of pre-attack symptoms (OR = 1.464, p = 0.044). Conclusions: Pre-attack symptoms were frequently observed in Korean patients with cluster headache, which was consistent with previous Western studies.